Erectile and sexual dysfunction in male and female patients with celiac disease: A cross‐sectional observational study. (26th April 2022) - Romano, Lorenzo; Pellegrino, Raffaele; Sciorio, Carmine; Barone, Biagio; Gravina, Antonietta Gerarda; Santonastaso, Antonio; Mucherino, Caterina; Astretto, Silvia; Napolitano, Luigi; Aveta, Achille; Pandolfo, Savio Domenico; Loizzo, Davide; et al.
Abstract: Introduction: Sexual function is often impaired in patients with chronic illnesses. Several patients with chronic gastrointestinal and liver disorders have been shown to suffer from sexual dysfunction, and celiac disease is a highly prevalent gastroenterological disorder. Aim: The aim of this study was to investigate the sexual function incidence and the risk factors for sexual dysfunction in both male and female celiac disease patients. Methods: Two hundred and eighty‐four patients (170 females, 114 males) participated in this cross‐sectional observational study in an anonymous manner. Female sexual function was assessed through the Female Sexual Function Index questionnaire. Male sexual function was assessed through the International Index of Erectile Function‐5 questionnaire. Clinical‐demographic variables were recorded. We investigated differences in the patient‐reported outcomes among the different subgroups and whether there were clinical‐demographic predictors of sexual dysfunction in our setting. Main outcome measures: Prevalence and assessment of sexual dysfunction in celiac disease patients. Results: In the female group, 85 subjects (50%) had a total score compatible with sexual dysfunction: 43 (61.42%) showed low desire, 79 (46.47%) showed arousal disorder, 66 (38.82%) lubrication disorder, and 84 (49.41%) inability of obtaining an orgasm. Also, a large proportion of our female patients, 161 (94.70%), showed sexual discomfort during intercourse. In the male group, 79 patients (62.2%) showed scores compatible with normal erectile function, eight (7.01%) had mild erectile dysfunction, 24 (21.05%) mild to moderate erectile dysfunction, and three (2.63%) presented severe erectile dysfunction. Altered body mass index was significantly associated with sexual dysfunction both in male and female patients. Early age at diagnosis was a significant predictor of sexual dysfunction in male celiac disease patients. Conclusions: A significant proportion of celiac disease patients present sexual dysfunction. Early age at diagnosis and high body mass index seem to predict sexual dysfunction in this clinical setting. Assessment of sexual function should be part of the initial evaluation of celiac disease patients in order to establish a prompt diagnosis and early treatment.